Kendala Dalam Pelaksanaan Pembelian Terselubung (Undercover Buy ) Dalam Mengungkap Tindak Pidana Narkotika Oleh Penyidik Polri - Iqbal Taufik (Faculty of Law, Universitas Pattimura, 2017)
Investigators have an important role in uncovering the crime of narcotics, one way is to use the technique of covert purchase (undercover buy). In the execution of investigators often encounter obstacles, including: lack of number of factors necessary equipment, limited operating costs, investigators get terror and be a witness in the trial, difficulties in getting the informant, constraints determine the location of purchase veiled, and drug network that uses techniques mines. Thus, efforts should be made to overcome these obstacles, namely: improving human resources and reporting in order to be fulfilled, submit the plan to increase the number of articles of association, the investigator must be professional in performing their duties, to optimize the role of a suspect or a courier who had been caught, locate covert purchases away from the community, and by making use of article 86 paragraph (2).